난황유와 공기순환팬의 상추 흰가루병 방제효과 및 생산에 미치는 영향 - 지형진(Hyeong-Jin Jee); 류경열(Kyung-Yul Ryu); 박종호(Jong-Ho Park); 최두회(Du-Hoe Choi); 류갑희(Gab-Hee Ryu); 류재기(Jae-Gee Ryu); 신순선(Shun-Shan Shen) (Sigmulbyeong yeon'gu, 2008)
Powdery mildew of lettuce that is a newly reported disease became a threat to organic cultivation of lettuce in Korea since the disease caused by Podosphaera fusca resulted in a half of yield loss in heavily infected fields. To improve micro-environmental conditions around lettuce, ACF (air-circulation fan) was installed on inside roof of plastic house at 6 m intervals. The ACF increased 57% of lettuce yield and reduced 71.4% of lettuce seedling death. COY (cooking oil and yolk mixture) consisted of cooking oil 0.3% and egg yolk 0.08% reduced lettuce seedling death from 89.3% to 92.9% under the greenhouse. Seven-day interval spray of COY resulted in high control values of powdery mildew of lettuce ranging from 89.6% to 96.3%, which was comparable to a fungicide, Azoxystrobin. Lettuce yield was increased about two times compared to a non-treated conventional cultivation. Qualities of lettuce such as hardness and chlorophyll content were also improved by COY and ACF combination. Effect of COY on control of the disease was improved when $CaCO_3$ or $SiO_2$ 1,000 ppm was supplemented. Results indicated that the COY made of cooking oil such as canola emulsified with yolk was highly effective on control of powdery mildew of lettuce and suitable for organic agriculture, especially when combined with ACF. Podosphaera fusca에 의한 상추 흰가루병은 최근에 보고된 새로운 병해이나 심하게 발생될 경우에는 수량을 50% 이상 감소시켜 유기농 상추재배에 큰 위협요인 되고 있다. 본 연구에서는 비닐하우스 내부에 소형의 공기순환팬을 6 m 간격으로 설치하여 상추 주변의 기상환경을 개선한 결과 수량 57% 증가와 정식묘 고사율 71.4% 감소 효과를 얻었다. 공기순환팬을 설치한 하우스에서 식용유를 계란노른자로 유화시킨 난황유 0.3% 용액을 처리한 경우에는 농가 관행재배 하우스에 비해 묘 고사율은 $89.3{\sim}92.9%$ 감소되었고 상추 흰가루병 방제효과는 89.6-96.3%로 매우 높게 나타나 살균제(azoxystrobin)와 대등하였다. 난황유 처리구별로 상추 수량은 $23.3{\sim}26.5\;kg$으로 대조 하우스의 11.86 kg과 비교할 때 약 2배 정도 높았고 상추 잎의 경도는 다소 낮고 엽록소 함량은 높아지는 등 상추 품질을 개선하는 효과도 나타났다. 본 연구 결과를 볼 때 채종유를 계란노른자로 유화시켜 만든 난황유는 상추 흰가루병 방제효과가 매우 높고 유기농 상추 생산에 유용하게 활용할 수 있을 것으로 기대되는데 공기순환팬을 설치하여 재배환경을 개선하면 상승효과를 얻을 수 있는 것으로 나타났다.